International Anarchy Revisited: A Critique on Waltz’s Interpretation of Rousseau - Karman, Mireille Marcia (UI Scholars Hub, 2018)
Kenneth Waltz is a celebrated scholar of International Relations whose works become the foundation of the neorealism camp in International Relations. One of his most prominent thesis is the existence of international anarchy, in which he calls the third image, makes a perpetual state if war in the inter-state relations. This essay does not examine whether his thesis is valid, instead it tries to problematize the use of Jean–Jacques Rousseau’s texts as the foundation in creating the third image perspective. I argue that Waltz misinterpretation on some of Rousseau’s texts makes his thesis on international anarchy and constant state of war do not align with Rousseau’s philosophical thoughts, despite the utilization of Rousseau’s text as the foundation of the thesis. I use the Hermeneutics methods to provide an alternative interpretation of Rousseau’s works and criticize Waltz’s interpretation of them.